2009
DOI: 10.3928/01477447-20090915-52
|View full text |Cite
|
Sign up to set email alerts
|

Cup Positioning in Primary Total Hip Arthroplasty Using an Imageless Navigation Device: Is There a Learning Curve?

Abstract: In this study, the success of cup positioning in total hip arthroplasty (THA) using an imageless navigation system was analyzed (1) during the learning period and (2) after the learning period for using the navigation system. Sixty THAs were performed in which threaded cups were placed with use of a computer-assisted navigation device (B. Braun Aesculap, Tuttlingen, Germany). Half of the procedures (30), group A, were done by the same surgeons under the learning curve for using the navigation system; the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Thorey et al [25] reported that navigation may lead to a reduction in the length of the learning curve, improve the surgeon's ability, and minimize outliers for inexperienced surgeons. However, whether navigation is useful in achieving precise placement of the cup regardless of the level of surgical experience remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thorey et al [25] reported that navigation may lead to a reduction in the length of the learning curve, improve the surgeon's ability, and minimize outliers for inexperienced surgeons. However, whether navigation is useful in achieving precise placement of the cup regardless of the level of surgical experience remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The costs associated with these devices can be prohibitive for some facilities, with capital costs reaching $250,000 and software/maintenance accounting for tens of thousands of dollars of additional costs per year [ 36 , 37 ]. Additionally, the learning curve associated with their use can require extended periods of time (up to 50 cases) before surgeons achieve proficiency [ 38 ]. Finally, while providing accurate measurements, these devices have been associated with significant increases in procedural time, ranging from 12 to 23 minutes per procedure [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thorey et al found a prolongation of the operative time to be 4.8±3.8 min after the learning curve (Thorey et al 2009). Thorey et al found a prolongation of the operative time to be 4.8±3.8 min after the learning curve (Thorey et al 2009).…”
Section: Evidence Of Benefits Using Navigationmentioning
confidence: 99%